1993
DOI: 10.1177/0013164493053001022
|View full text |Cite
|
Sign up to set email alerts
|

Academic Self-Concept and its Relationship to Achievement in a Sample of Junior High School Students

Abstract: This study examined the relationship of academic self-concept to achievement for a sample of junior high school students. Academic self-concept was found to correlate significantly more strongly with achievement than general self-concept, motivation, and class- room behavior, but not with locus of control. The results of a multiple regression analysis, however, indicated that academic self-concept was approximately twice as powerful a predictor of achievement as locus of control. These results are discussed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
3
18
0
5
Order By: Relevance
“…Research suggests that as much as one third of the variance in achievement can be accounted for by academic selfconcept alone (Lyon, 1993). Our own research (McCoach & Siegle, in press, b) suggests that the academic self-perceptions subscale of the S AAS-R accounts for approximately 20% of the variance in students' self-reported GPA.…”
Section: Review Of the Literaturementioning
confidence: 68%
See 1 more Smart Citation
“…Research suggests that as much as one third of the variance in achievement can be accounted for by academic selfconcept alone (Lyon, 1993). Our own research (McCoach & Siegle, in press, b) suggests that the academic self-perceptions subscale of the S AAS-R accounts for approximately 20% of the variance in students' self-reported GPA.…”
Section: Review Of the Literaturementioning
confidence: 68%
“…Social comparison theory suggests that when people compare favorably to those around them in a particular domain, they are more likely to maintain high self-concepts in that domain. Academic self-concept is a significant predictor of academic achievement (Lyon, 1993;Marsh, Chessor, Craven, & Roche, 1995;Wigfield & Karpathian, 1991); however, it is negatively related to the average achievement level within a school (Marsh, 1987). This implies that students' academic self-concepts are determined by their perceptions of their ability in an area as well as their assessment of their academic standing relative to their classmates.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Pri tome se, pre svega, misli na onaj vid motivacije koji pojedini autori nazivaju posvećenost zadatku ili orijentacija na zadatak, a koji se prevashodno manifestuje kroz spremnost na ulaganje velikog truda i napora u ovladavanju određenim domenom, te perzistenciju u obavljanju ovih aktivnosti i pored nailaženja na brojne prepreke (Ames, 1992). U vezi sa motivacionim svojstvima, kao činiocima koji dobro predviđaju uspešnost u određenom domenu, je i konstrukt self-koncepta, tačnije "akademskog self-koncepta" (Lyon, 1993) ili "selfkoncepta u odnosu na sposobnosti" (Bloom, 1976, prema Trost, 2000. Selfkonceptu se pripisuje neka vrsta posredujućeg delovanja između sposobnosti i motivacije i u pojedinim istraživanjima je ustanovljeno postojanje visoke po-vezanosti ovog konstrukta sa uspešnošću u različitim domenima (Marsh et al, 1995, prema McCoach, 2002, koja sugeriše da self-koncept objašnjava čak trećinu varijanse kriterijumske varijable (Lyon, 1993).…”
Section: Inteligencija I Osobine Ličnosti Kao Prediktori Uspešnosti Munclassified
“…Lyon (1993) highlighted the importance of the relationship between SC and academic achievement, and stated that -academic self-concept is theoretically more closely related to academic achievement than most other cognitive variables‖ (p. 203). Marsh, Parker, and Barnes (1985) indicated that the substantial correlations between different areas of SC and academic ability and performance measures provide evidence for the construct validity of SC.…”
mentioning
confidence: 99%